2006
DOI: 10.1097/01.bsd.0000211241.06588.7b
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage Transpedicular Decompression and Posterior Instrumentation in Treatment of Thoracic and Thoracolumbar Spinal Tuberculosis

Abstract: The posterior decompression with transpedicular instrumentation can be an alternative treatment method of less-involved spinal tuberculosis especially for patients in early phase of bone destruction or ones with mild kyphosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 33 publications
4
87
0
1
Order By: Relevance
“…Some scholars have expressed concern that lesions confined to the vertebral body could spread to the lamina of the vertebra and spinous process to result in infectious meningitis. However, standard antituberculosis chemotherapy can prevent recurrence and metastasis of tuberculosis [4,18,19], while the current relevant literature and our study show that such complications are rare [19,20]. Compared with patients treated with anterior approach, patients treated with posterior approach are more conducive to drainage of residual lesions postoperatively in the supine position because of gravity.…”
Section: Discussionmentioning
confidence: 68%
“…Some scholars have expressed concern that lesions confined to the vertebral body could spread to the lamina of the vertebra and spinous process to result in infectious meningitis. However, standard antituberculosis chemotherapy can prevent recurrence and metastasis of tuberculosis [4,18,19], while the current relevant literature and our study show that such complications are rare [19,20]. Compared with patients treated with anterior approach, patients treated with posterior approach are more conducive to drainage of residual lesions postoperatively in the supine position because of gravity.…”
Section: Discussionmentioning
confidence: 68%
“…These authors have used segmental spinal instrumentation with pedicle screws and rods. In most of these reports, additional procedures such as posterior closing wedge osteotomy, and posterior inter-body fusion using bone grafts with or without cages have been performed [37,[39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is one report comparing the anterior approach with the posterior approach for spinal tuberculosis. Lee et al [5] reported their experiences with the anterior or posterior approaches combined with internal fixation for thoracolumbar tuberculosis. They concluded that there was no difference in outcomes between groups and that the posterior approach was useful for treating early-diagnosed thoracic and thoracolumbar spinal tuberculosis for the following indications: (1) <50% collapse of the vertebral body, and (2) mild kyphosis (<30°).…”
Section: Group (N)mentioning
confidence: 99%
“…Posterior instrumentation has become popular as a technique to correct angular deformities and stabilise an unstable spine. Several authors have reported that the use of the posterior approach combined with debridement and instrumentation to treat spinal tuberculosis has led to favourable clinical outcomes [5][6][7]. However, the posterior approach remains controversial because it may affect posterior spinal column stability [8,9].…”
Section: Introductionmentioning
confidence: 99%